Justifying sustainability - Geir B. Asheim; Wolfgang Buchholz; Bertil Tungodden (University of Oslo, Department of Economics, 1999)
In the framework of ethical social choice theory, sustainability is justified by Efficiency and Equity as ethical axioms. These axioms correspond to the Suppes-Sen Grading principle. In technologies that are productive in a certain sense, the set of Suppes-Sen maximal utility paths is shown to equal the set of non-decreasing and efficient paths. Since any such path is sustainable, Efficiency and Equity can thus be used to deem any unsustainable path as ethically unacceptable. This finding is contrasted with results that seem to indicate that an infinite number of generations cannot be treated equally. – Sustainability ; Ethical Preferences ; Suppes-Sen Grading principle
Keywords: D63; Q32; 330; Nachhaltige Entwicklung; Ethik; Soziale Wohlfahrtsfunktion; Generationenbeziehungen; Gerechtigkeit; Theorie